(untitled) (Pulse, 2018)
A 5 years old boy with multiple café au lait spots came with intermittent weakness of the right side of the body and seizures. The child had global developmental delay. His MRI and MRA showed thickening of the optic nerves, abnormal signal in multiple areas of the brain with non-visuation of the left middle cerebral artery. The child was diagnosed to have neurofibromatosis type 1 with seizures with bilateral optic glioma with Moya Moya disease. Pulse Vol.10 January-December 2017 p.34-37